Comparative expression profile of developmental related genes in haploid and diploid parthenogenetic embryos in caprine - SINGH, RENU; KUMAR, KULDEEP; KHAN, IRAM; RANJAN, R; T, YASOTHA; SINGH, R K; DAS, B C; BAG, SADHAN (The Indian Journal of Animal Sciences, 2013)
Several reports suggested that haploid parthenogenetic embryos have less developmental ability as compared to diploid parthenogenetic or IVF derived embryos, may be due to lesser expression of developmental related genes. The present study was, therefore, carried out to compare expression of early embryonic developmental related genes in different stages of haploid and diploid parthenogenetic embryos in goat. Good quality oocytes were aspirated from the ovary and matured in maturation medium without (haploid embryo generation) or with cytochalasin B (for diploid embryo generation). After maturation, oocytes were activated using ionomycin followed by incubation with 6-DMAP in mSOF. The activated oocytes were further cultured in mSOF for generation of parthenogenetic embryos of different stages. Total RNA was isolated from pool of, viz 2–4, 8–16 and morula cell stages embryos of haploid and diploid, respectively, and cDNA was synthesized. The relative expression of Nanog, Sox-2, Klf4 and Foxd3 genes were analyzed by real time PCR. The result indicated that the relative expression of all 4 genes could not be detected in 2–4 and 8–16 cell stage of haploid embryos, whereas 2–4 and 8–16 cell stage diploid embryos expressed all these genes. When both type of embryos reached at morula stage, the expression of all the genes were present and no significant changes were observed between haploid and diploid parthenogenetic embryos. From the results, it can be concluded that haploid parthenogenetic embryos showed undetectable level of embryonic develpomenta lrelated genes like Nanog, Sox-2, Klf4 and Foxd3 at early embryonic develpomental stage in comparison to diploid parthenogenetic embryos. This may be one of the major reasons for poor developmental competence of parthenogenetic haploid embryos.